The Relationship between Economic Growth and Carbon Emissions in South Africa - Khobai, Hlalefang; Sithole, Katlego (International Journal of Energy Economics and Policy, 2022)
South Africa has been dismantling the challenges of Global warming and climate change issues pertaining Carbon emissions which have aggravated environmental problems over the past years due to its heavy reliance on coal. About 77% of South Africa's electricity needs are been bestowed by coal. This study serves to determine the relationship between carbon emissions and economic growth in South Africa covering the period between 1984 and 2018. The study employed the ARDL bounds technique to determine the long run relationship among the variables and the VECM to determine the direction of causality among variables. The findings established that there is a long relationship between carbon emission, economic growth, energy consumption, foreign direct investment and trade openness in South Africa. The VECM suggested that there is bidirectional causality flowing between economic growth and carbon emissions. The results also validated the EKC hypothesis both in the long run and short run. It is thus imperative for the policy makers and government to divert their thoughts to more innovative and creative strategies of attaining alternative energy sources especially renewable sources. There is a need for the best environmental policy to enhance infrastructure investment to improve energy efficiency and reduce emissions.